SOSIALISASI DISIPLIN DAN PELAYANAN PUBLIK APARATUR DESA KALIJAGA SELATAN, KEC. AIKMEL, LOMBOK TIMUR - Muh. Nizar; Lalu Amrullah; Nasrullah Nasrullah (LPPM Institut Pendidikan Nusantara Global, 2026)
The promotion of discipline and public service is a strategic step in improving the performance quality of village officials. As the spearhead of government, village officials play a crucial role in providing services to the public in a professional, transparent, and accountable manner. This outreach activity aims to increase village officials' understanding of the importance of work discipline and public service standards in accordance with applicable regulations. The implementation method is carried out through counseling, interactive discussions, and evaluation of participant understanding. The results of the activity indicate an increase in village officials' understanding of the importance of discipline, service ethics, and the application of effective and efficient public service principles. This activity is expected to create better village governance and increase public satisfaction with the services provided.